2000
DOI: 10.1089/thy.2000.10.815
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Serum lnterleukin-18 in Graves' Disease

Abstract: We have previously reported that serum soluble interleukin-2 receptor (sIL-2R) and IL-12 levels were significantly increased in hyperthyroid Graves' disease. In this study, we investigated serum IL-18 levels in patients with either Graves' disease or Hashimoto's thyroiditis. The serum IL-18 levels in Graves' disease were significantly increased in the hyperthyroid state and were decreased during treatment with methimazole or propylthiouracil. On the other hand, the levels in Hashimoto's thyroiditis in the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
4
26
1
Order By: Relevance
“…In this regard, increased serum IL-18 levels have been described in patients with Graves' disease, but not after liothyronine treatment in euthyroid individuals (28). To our knowledge, we describe here for the first time a thyroxinedependent increase in serum IL-18 levels in an in vivo human model in which autoimmunity is not involved.…”
Section: Discussionmentioning
confidence: 53%
“…In this regard, increased serum IL-18 levels have been described in patients with Graves' disease, but not after liothyronine treatment in euthyroid individuals (28). To our knowledge, we describe here for the first time a thyroxinedependent increase in serum IL-18 levels in an in vivo human model in which autoimmunity is not involved.…”
Section: Discussionmentioning
confidence: 53%
“…Recent research showed that methimazole moderately inhibited the synthesis of immunoglobulins including TSAb (14)(15)(16)(17)(18)(19)(20). In this study, we treated GO and GD patients with methimazole and examined the effect of the drug on the T cell subgroups, the populations of Th1 and Th2 cells, and the Th1/Th2 cell ratio in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…IL-18 is not up-regulated in patients suffering from Hashimoto's thyroiditis (29), although such patients do have elevated IFN-␥ levels (see above). In mammals, IL-18 has three main roles: to induce IFN-␥ production (30), to enhance NK cell activity (31), and to activate neutrophils (32).…”
Section: Discussionmentioning
confidence: 97%